(untitled) (Journal of the College of Basic Education, 2022)
The current study highlight on the changes that occurred in rivers in their natural balance after building dams and reservoirs، and that studies in this field are few. This topic was focused on the following fields: 1.Structural work in rivers that includes the formation of flood or alluvial fans. The flood plains، the delta، through the sediment of the river during the floods. 2.Building dams and reservoirs and their impact on the forms formed by rivers by reserving water in the dam lake، which affects the construction work of the rivers. 3.Uses of dams and reservoirs and their importance through hydroelectric generation and other modern applications and uses that indirectly affect the nature of the river by creating a new environment that differs from the original environment of the river before the emergence of dams and reservoirs. 4.The construction of dams and reservoirs slowed down the progress of the delta and negatively affected soil fertility and increased the river’s ability to dredge its course and its impact on the quality of groundwater in the dam and reservoir area. From the current study، we conclude that the construction of dams and reservoirs can have a positive dual impact on the one hand through its impact on contemporary life and negative through a change in the nature of the original river environment